ChemInform Abstract: Radical N‐Arylation/Alkylation of Sulfoximines. Issue 38 (September 2016) - Zhu, Hui; Teng, Fan; Pan, Changduo; Cheng, Jiang; Yu, Jin‐Tao
Abstract: A facile protocol is developed for the copper catalyzed reaction of sulfoximes with acyl peroxides as aryl/alkyl source to form the corresponding N‐arylated or N‐alkylated products.